A procedure for the analysis of site‐specific and structure‐specific fucosylation in alpha‐1‐antitrypsin. Issue 20 (5th September 2016) - Yin, Haidi; Zhu, Jianhui; Wu, Jing; Tan, Zhijing; An, Mingrui; Zhou, Shiyue; Mechref, Yehia; Lubman, David M.
Abstract : A MS‐based methodology has been developed for analysis of core‐fucosylated versus antennary‐fucosylated glycosites in glycoproteins. This procedure is applied to the glycoprotein alpha‐1‐antitrypsin (A1AT), which contains both core‐ and antennary‐fucosylated glycosites. The workflow involves digestion of intact glycoproteins into glycopeptides, followed by double digestion with sialidase and galactosidase. The resulting glycopeptides with truncated glycans were separated using an off‐line HILIC (hydrophilic interaction liquid chromatography) separation where multiple fractions were collected at various time intervals. The glycopeptides in each fraction were treated with PNGase F and then divided into halves. One half of the sample was applied for peptide identification while the other half was processed for glycan analysis by derivatizing with a meladrazine reagent followed by MS analysis. This procedure provided site‐specific identification of glycosylation sites and the ability to distinguish core fucosylation and antennary fucosylation via a double digestion and a mass profile scan. Both core and antennary fucosylation are shown to be present on various glycosites in A1AT.